2010
DOI: 10.1007/s10815-010-9439-y
|View full text |Cite
|
Sign up to set email alerts
|

Overweight Men: clinical pregnancy after ART is decreased in IVF but not in ICSI cycles

Abstract: Purpose To evaluate if elevated male body mass influences success after assisted reproductive technologies Methods Retrospective study of 290 cycles. Results Male body mass index greater than 25.0 kg/m 2 was associated with significantly lower clinical pregnancy (53.2% vs. 33.6%). Multivariable logistic regression indicated that the likelihood of clinical pregnancy was decreased if the male partner was overweight after in vitro fertilization but not after intracytoplasmic sperm injection (odds ratios: 0.21 [0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
101
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(107 citation statements)
references
References 43 publications
(45 reference statements)
5
101
0
1
Order By: Relevance
“…[27][28][29][30] Recent evidence from both animal and human studies indicates that male obesity and high-fat diets result in impaired reproductivity, affecting the molecular and physical structure of sperm as well as the health of the developing fetus and subsequent offspring. 27,[31][32][33][34][35][36][37][38][39] In a recent animal study, Rato et al 39 reported that the testicular physiology is sensitive to alterations of whole-body metabolism and that the testicular metabolism can be disturbed by high-energy diets. Disruption of testicular metabolism is associated with decreased sperm quality.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30] Recent evidence from both animal and human studies indicates that male obesity and high-fat diets result in impaired reproductivity, affecting the molecular and physical structure of sperm as well as the health of the developing fetus and subsequent offspring. 27,[31][32][33][34][35][36][37][38][39] In a recent animal study, Rato et al 39 reported that the testicular physiology is sensitive to alterations of whole-body metabolism and that the testicular metabolism can be disturbed by high-energy diets. Disruption of testicular metabolism is associated with decreased sperm quality.…”
Section: Introductionmentioning
confidence: 99%
“…More than one-third of men of reproductive age in the United States are classified as obese [1]. Paternal obesity not only impairs male fertility by impacting sperm count, motility and chromatin integrity [2][3][4][5][6][7] but also reduces subsequent embryo development, implantation rates, pregnancy success and live birth rates [8][9][10][11][12]. Interestingly metabolic syndrome, which includes obesity, in fathers is associated with polycystic ovary syndrome in daughters [13].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the rates of male obesity in reproductive age men has nearly tripled since the 1970s (33). Recent studies in both humans and other species shows that male obesity impairs male reproductive potential, affecting both the molecular and physical structure of sperm (1,10,16,20,21,34,35,38,45,47,50,63,75,79) and the health of the developing fetus and subsequent offspring (9,24,42,55,59). …”
mentioning
confidence: 99%
“…There is a negative impact of male obesity on standard semen parameters, including motility, count, and hormone abundance, such as testosterone and inhibin B (1,5,16,18,21,22,32,35,37,45,47,52,62,69,85). Further studies have reported reduced pregnancy success and live birth outcomes after IVF treatment in overweight and obese men (9,42).…”
mentioning
confidence: 99%